Students' Perceptions of English Development Program on Their Speaking Skill at Islamic Boarding School - Salsabila, Syarifah; Nugraheni, Dyah Ayu (Linguapedia, 2024)
The purpose of this study was to determine students' perceptions of the English Development Program on students' speaking skills. English Development Program is a program established to help students learn English better, especially in terms of speaking. The subjects of this study were 4 students from Pesantren Nuris who participated in the English Development Program selected by pursosive sampling. This research uses qualitative methods, and the research instrument uses interviews. The interview results show that the majority of students have a positive perception of the English Development Program. The students believe that the English program can support them to speak English fluently. Students also have the perception that the English program is a place for students to develop their English skills, especially in terms of speaking. Not only that, students also think that the English program can make them more confident in speaking English.